Adsorption Study for Trifluralin on Iraqi Zeolite - Mahmood, Zahraa A (Al-Nahrain Journal of Science, 2018)
The current work involves the adsorption of trifluralin on the surface of zeolite using UV. spectrophotometer technique to produce quantitative adsorption data at different conditions of contacttime, ionic strength, pH and temperatures. The adsorption phenomenon was examined as a function of temperatures (30, 35, 40, and 45) ˚C, and the results showed that the adsorption of trifluralin on surface zeolite increased with increasing temperatures (endothermic process). The basic thermodynamic functions (∆H, ∆G, and ∆S) have also been calculated. The effect of ionic strength on adsorption was also studied by using different concentrations of NaCl solution. It was found that increasing the value of ionic strength, leads to decrease the adsorption quantity of trifluralin on the zeolite surfaces at constant temperature. The quantity of trifluralin that was adsorbed on the zeolite was decreased with increasing the pH of the solution at constant temperature. The kinetic study of adsorption process was studied depending on the following kinetic equations: Lagergren, Morris –Weber and Reichenenberg equations.